Pathways of Identity: Sustainable Campus Signage with Digital Integration - Khairini, Yulika; Barliana, Dhea Fatha; Trie Putra, Priambudi; Indira, Sri Shindi (Graduate School, Universitas Brawijaya, 2026)
The growing need for dependable navigation across the National Institute of Science and Technology (ISTN) emerges as the campus environment becomes more complex. As a higher-education institution in Jakarta, the National Institute of Science and Technology continues to expand its academic and spatial functions, prompting demand for a cohesive wayfinding system that supports daily mobility and reinforces institutional branding. This study adopts a qualitative descriptive approach, grounded in site observation, movement pattern analysis, and the identification of recurring disorientation points, to examine existing navigational conditions across the campus. Based on these findings, a structured and user-focused signage framework is developed to enhance circulation clarity and visual coherence. Readability, consistency, and legibility form the basis of the design strategy, while institutional identity is expressed through controlled formal language, legible typography, and differentiated color cues that assist users in recognizing faculties, departments, and key facilities. Beyond physical signage, the system integrates QR codes to extend navigational and institutional information without disrupting the existing spatial structure. Through this integrated approach, the proposed wayfinding system improves campus legibility while subtly reflecting institutional values embodied in the institution’s motto Wedha Wiyata Wira Sakti, resulting in a coherent, inclusive, and forward-looking campus environment that balances identity, technology, and sustainability